The pocketbook for physiotherapists - Amrohit, Gitesh (Jaypee Brothers Medical Publishers, 2011)
.An informative pocketbook. Maximally expanded and added with latest information. Deals with all the important stuffs related to medicine and physiotherapy. Explains facts with the help for graphs, table and test without modifying the original meaning. Includes a lot of normal values, special tests, drugs, pathology, anatomy, and various other things. Helpful for undergraduates, postgraduates and professionals of physiotherapy.